2013
DOI: 10.1097/dcr.0b013e31828aedcb
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Surgery After Long-Course Neoadjuvant Chemoradiotherapy for Rectal Cancer

Abstract: There is limited evidence to support decisions regarding when to resect rectal cancer following chemoradiotherapy. There may be benefits in prolonging the interval between chemoradiotherapy and surgery beyond the 6 to 8 weeks that is commonly practiced. However, outcomes need to be studied further in robust randomized studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 33 publications
3
56
0
1
Order By: Relevance
“…In these cases pre-operative MR may not only direct surgical dissection, but also alert the MDT to the need for further upfront systemic chemotherapy, contact radiotherapy or extended surgical resection. In this cohort of patients, the identification of an optimal time for surgery post-NACRT which coincides with maximal oncological down-staging is an urgent question [21,31]. This pilot study suggests that further volume reduction and down-staging occurs between Week 9 and Week 14 post-NACRT, with more favourable ymrT, ymrTRG and volume changes found at Week 14.…”
Section: Interobserver Agreementmentioning
confidence: 80%
See 1 more Smart Citation
“…In these cases pre-operative MR may not only direct surgical dissection, but also alert the MDT to the need for further upfront systemic chemotherapy, contact radiotherapy or extended surgical resection. In this cohort of patients, the identification of an optimal time for surgery post-NACRT which coincides with maximal oncological down-staging is an urgent question [21,31]. This pilot study suggests that further volume reduction and down-staging occurs between Week 9 and Week 14 post-NACRT, with more favourable ymrT, ymrTRG and volume changes found at Week 14.…”
Section: Interobserver Agreementmentioning
confidence: 80%
“…In addition to these assessment criteria, the MERCURY study group has developed an MRI-based tumor regression grading (ymrTRG) system by applying the principles of histopathology ypTRG [17,18] and showed that MRI assessment of ypTRG following preoperative therapy predicted survival [17]. It has been suggested that there may 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 be benefits in prolonging the interval between end of NACRT and surgery beyond the common 6-8 weeks [19][20][21], but evidence is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor shrinkage in response to radiotherapy is often not apparent radiologically until several weeks after treatment completion [5]. The radiation dose and degree of tumor response required to palliate different pelvic symptoms is unknown, but a recent systematic review of palliative pelvic radiotherapy (PPRT) of RC found symptomatic improvement across a wide range of treatment schedules [2].…”
mentioning
confidence: 99%
“…They found limited evidence to support decisions regarding when to resect rectal cancer following chemo-radiotherapy. There may be benefits in prolonging the interval between chemoradiotherapy and surgery beyond the 6 to 8 weeks that is commonly practiced (10). However, there are also data which do not show any down-staging.…”
Section: Discussionmentioning
confidence: 86%